2018
DOI: 10.24313/jpbl.2018.5.1.29
|View full text |Cite
|
Sign up to set email alerts
|

The effects of flipped learning on learning motivation and attitudes in a class of college physical therapy students

Abstract: Purpose: This study aims to verify the effects of flipped learning on learning motivation and attitudes in a class of college physical therapy students. Methods: The subjects were 97 students in College A who had registered for musculoskeletal examination and assessment and practice at the second semester of 2017. The flipped learning program was applied to students for one semester, after which a paired t-test was performed to compare the dependent variables (learning motivation and attitudes) before and afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
16
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 18 publications
2
16
0
2
Order By: Relevance
“…Indeed, no one can deny that motivation plays an effective role in the learning process. The present positive results are consistent with the findings of numerous studies referred to in the literature (Abeysekara & Dawson, 2015;Akçayır & Akçayır, 2018;Al-Zahrani, 2015;Bergmann & Sams, 2012;Chung & Lee, 2018;Cole & Kritzer, 2009;Deckers, 2018;Demirel, 2016;Gayeta, 2017;Johnson et al, 2016;Jyothia & Penman, 2017;Su & Chen, 2018;Tütüncü & Aksu, 2018).…”
Section: Flipped Classroom Impact On Students' Motivationsupporting
confidence: 92%
See 1 more Smart Citation
“…Indeed, no one can deny that motivation plays an effective role in the learning process. The present positive results are consistent with the findings of numerous studies referred to in the literature (Abeysekara & Dawson, 2015;Akçayır & Akçayır, 2018;Al-Zahrani, 2015;Bergmann & Sams, 2012;Chung & Lee, 2018;Cole & Kritzer, 2009;Deckers, 2018;Demirel, 2016;Gayeta, 2017;Johnson et al, 2016;Jyothia & Penman, 2017;Su & Chen, 2018;Tütüncü & Aksu, 2018).…”
Section: Flipped Classroom Impact On Students' Motivationsupporting
confidence: 92%
“…The results showed that students in the experimental group overcome those in the control group in terms of the four dimensions of ARCS. Correspondingly enough, Chung and Lee (2018) investigated the impact of the flipped model on learning motivation and attitudes in a class of college physical therapy students. Their fallouts displayed significant differences in learning motivation (attention, relevance, confidence, satisfaction) and attitudes toward physical therapy.…”
Section: / 16mentioning
confidence: 99%
“…Research conducted by Pavanelli (2018) on 22 students at Southern State College in the USA regarding their perception of flipped classrooms showed that 92% liked the flipped classroom model; 62% believed flipped classrooms were better than traditional ones; 70% agreed that it was easy to understand the material in a flipped classroom approach; 92% liked watching lessons on video; 77% agreed that video lessons helped understand the topics being studied, give students more time to practise and work on problems with friends, thus providing more significant opportunities for communicating with peers and teachers; 85% agreed that the flipped classroom model was a fun learning model; and 77% stated that the flipped classroom motivated them to learn more. These findings are supported by several studies that have proven that flipped classrooms are more attractive than traditional ones (Goedhart et al, 2019;Havwini & Wu, 2019;Herlindayana et al, 2017;Li et al, 2018;Paek & Fulford, 2017;Tomas et al, 2019); can motivate students to learn (Chung & Lee, 2018;Nouri, 2016;Su & Chen, 2018); and can help students to understand the concept of learning well (Nwosisi et al, 2016). Herlindayana et al (2017) conducted their study at a high school, showing that 75% of students agreed that the flipped classroom learning model could improve independent learning.…”
mentioning
confidence: 82%
“…The literature review found that the "Flipped classroom" learning concept has been studied as an integrated technical, instructional and psychological phenomenon (Panopto, 2015;Educause, 2012;Bykonia et al, 2019;Chung & Lee, 2018) which is referred as a multi-tool approach and is capable to change the perception of teacher and learner roles. It this study, the flipped classroom will be addressed as an instructional model taking advantage of the use of extracurricular time to engage the students in out-of-class activities to do all sedentary work before the class.…”
Section: The "Flipped Classroom" and Espmentioning
confidence: 99%